Analysis Of the Structure of Music Penanian Dolo Mesa'ri Tendan Lamatoto' Song - Sostenes Mono Tandililing; Sunarto Sunarto; Widodo Widodo (Gondang: Jurnal Seni dan Budaya, 2023)
Penanian Dolo This is a spiritual song brought by evangelists from the Netherlands along with the Dutch colonial events in Tana Toraja. Penanian Dolo is a song or song that was originally used in the liturgy of Christian worship in Tana Toraja. Over time, Penanian Dolo was used by the people of Gandangbatu in the procession of carrying the corpse (Ma'bulle Tomate).This study aims to determine the form and structure of Penanian Dolo music, Mesa'ri Tendan Lamatoto'. The research method used in this research is qualitative research using sociology and musicology approaches. The results of the study show that Penanian Dolo music, the song Mesa'ri Tendan Lamatoto'is a one-part song form with a total of 8 bars composed of one sentence/period. The song Mesa'ri Tendan Lamatoto' has two clauses, namely interrogative sentences/antecedent phrases (bars 1 – 4) and answer sentences/consequences phrases (bars 5 – 8). Each has the same number of bars but in the consequence phrase motif there are sentence pieces that are not the same length, in other words, they are not symmetrical. This can happen because the division of motifs must pay attention to the integrity of a sentence because the unity of the sentence is more important than the importance of each tone. The motif of the song begins with a tonic chord and ends with a dominant chord to a tonic chord (perfect cadences). The development of dominant motifs uses repetition techniques. The rhythm used in the song Mesa'ri Tendan Lamatoto' uses three types of note values, namely not , notes ¼ and notes 1/8 . The measure or beat pattern used in Mesa'ri Tendan Lamatoto's song uses 4/4 measure, which means that there are four quarter notes in one measure. The tempo used in Mesa'ri Tendan Lamatoto song is moderato which means moderate with a speed of 92-104 beats per minute. The melody used in the Penanian Dolo song as a whole uses diatonic scales. On the other hand, the lyrics in Mesa'ri Tendan Lamatoto' contain aspects of worship and surrender to the almighty. The melody used in the song Penanian Dolo as a whole uses a diatonic scale. On the other hand, the poems in the song Mesa'ri Tendan Lamatoto' contain aspects of worship and submission to the almighty. The melody used in the Penanian Dolo song as a whole uses diatonic scales. On the other hand, the lyrics in Mesa'ri Tendan Lamatoto' contain aspects of worship and surrender to the almighty.